A Phenomenological Investigation of the Interplay Among Professional Worth Appraisal, Self-Esteem and Self-Perception in Nurses: The Revelation of an Internal and External Criteria System - Karanikola, Maria; Doulougeri, Karolina; Koutrouba, Anna; Giannakopoulou, Margarita; Papathanassoglou, Elizabeth D. E. (Frontiers in Psychology, 2018)
Nurses’ professional self-concept is strongly associated with professional worth appraisal, which encompasses their feelings and perceptions regarding their task efficacy and value of input to clinical outcomes. Professional self-concept and professional worth appraisal are incorporated in one’s overall professional role perception. Data show that the way nurses think and feel about themselves personally and professionally, is associated with their well-being, the quality of provided patient care, their job satisfaction and retention. Although researchers indicate that professional self-concept is a different entity from personal self-concept, however a clear differentiation and possible interaction between these constructs have not yet been adequately described in nursing literature. Personal self-concept mirrors the way people think about them-selves, incorporating their self-awareness and personal worth appraisal. Following purposeful sampling and informed consent, a phenomenological approach based on Munhall’s methodology was employed to explore the living experience of professional role perception in 18 hospital nurses, with special focus on their perceptions and feelings about personal and professional-role worth appraisal. Data and theoretical saturation criteria were implemented, along with all nine Munhall’s criteria for the rigour and trustworthiness of phenomenological studies. The participants’ narratives suggested a possible interaction between professional attitude and personality traits, illuminating as the core theme an interplay among self-perception, personal and professional worth appraisal process. Additionally, the present study emphasized the way self-evaluation criteria system may be associated with the personal and professional self-concept in nurses. In particular, it was highlighted that the way nurses think and feel about themselves is associated with the way they experience their professional role and vice versa, and that professional role-based self-concept and professional worth perception can be linked with their well- being. Furthermore, positive feelings about the self and personal competencies seemed to enhance the perception of effectiveness in clinical settings and adequacy of professional skills, resulting in increased professional worth perception, and vice versa. Overall, the present findings are discussed in relation to nurses’ resilience towards work-related stressors and burnout syndrome. Further exploration of the self-appraisal process in nurses, regarding their personal and professional role, as well as the association with adverse work-related phenomena is suggested.